De Ibsen a Genet: la rebelión en el teatro - Brustein, Robert
Contiene: Henrik Ibsen, August Strindberg, Anton Chejov, Bernard Shaw, Bertolt Brecht, Luigi Pirandello, Eugene O'Neill, Antonin Artaud y Jean Genet: el teatro de la crueldad